Antioxidant peptides from marine by-products: Isolation, identification and application in food systems. A review. (March 2016) - Sila, Assaad; Bougatef, Ali
Highlights: Marine by-products as a source of antioxidant peptides. Production of antioxidant peptides by enzymatic hydrolysis. Isolation and identification of antioxidant peptides. Abstract: In recent years, several attempts have been made for the utilisation of the protein rich fish processing by-product discards and underutilised fish proteins for the production of commercially valuable food ingredients. There has been an increasing interest in the utilisation of marine products, and novel bioprocessing technologies are developing for isolation of some bioactive substances. Antioxidant peptides isolated from marine food products have been used as functional foods and nutraceuticals. Peptides obtained by enzymatic hydrolysis of fish proteins exhibit not only nutritional but also biological properties for use in diet or in therapeutic purposes. In this review, we have focused on the enzymatic process for generating antioxidant peptides from marine by-products as well as on the isolation procedures of selected antioxidant peptides.